1999
DOI: 10.1115/1.483173
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of MCrAlY Coatings Sprayed by High Velocity Oxygen-Fuel Spraying System

Abstract: High velocity oxygen-fuel (HVOF) spraying system in open air has been established for producing the coatings that are extremely clean and dense. It is thought that the HVOF sprayed MCrAlY (M is Fe, Ni and/or Co) coatings can be applied to provide resistance against oxidation and corrosion to the hot parts of gas turbines. Also, it is well known that the thicker coatings can be sprayed in comparison with any other thermal spraying systems due to improved residual stresses. However, thermal and mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 9 publications
3
28
0
1
Order By: Relevance
“…There were difficulties, however, in relating curvature measurements of coating-substrate couples to actual coating stresses on thick, nonbending substrates. Similar effects of HVOF spray parameters have been reported for other material and spray systems, [18,[28][29][30] although spray particle characteristics are frequently not quantified.…”
Section: Introductionsupporting
confidence: 65%
“…There were difficulties, however, in relating curvature measurements of coating-substrate couples to actual coating stresses on thick, nonbending substrates. Similar effects of HVOF spray parameters have been reported for other material and spray systems, [18,[28][29][30] although spray particle characteristics are frequently not quantified.…”
Section: Introductionsupporting
confidence: 65%
“…MCrAlY, where M means Co and/or Ni, coatings have been developed to protect gas turbine blades from oxidation and corrosion at high temperature. 1) Itoh et al 2,3) systematically investigated the mechanical properties of MCrAlY coatings by both four points bending test and resonance method. However, the mechanical properties of the thin MCrAlY coatings used in actual turbine system were unknown, because there was not a proper measurement method of thin sprayed coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high kinetic energy of the particles, the high velocity oxy-fuel (HVOF) process leads to dense coatings. Furthermore, it has been confirmed that MCrAlY coatings can be produced by HVOF spraying with equivalent mechanical properties to vacuum plasma sprayed MCrAlY coatings ( Ref 4,5). Therefore the developed powder will be sprayed by the HVOF system.…”
Section: Introductionmentioning
confidence: 78%